Логістичне управління ресурсами: вплив на зменшення витрат та підвищення продуктивності - Пальчик, Ігор Миколайович; Palchyk, Ihor (Львівський університет бізнесу та права, 2023)
У 21 столітті ефективність, мабуть, є найціннішою річчю. Очевидно, щозниження витрат має прямий зв'язок з підвищенням ефективності. В даний час управління логістикою в усіх галузях промисловості широко обговорюється. Оскільки кожна ланка ланцюга поставок є важливою, а складські витрати - це зовсім не маленька цифра. Це стосується як підприємств-постачальників, так і логістичних компаній. Досягнення зниження складських витрат має важливе значення. Метою даного дослідження є дослідження методів оптимізації логістичного управління через складське управління та вплив на зниження витрат операційної діяльності підприємств. In the 21st century, efficiency is perhaps the most valuable thing. Obviously, cost reduction is directly related to efficiency improvement. Currently, logistics management in all industries is widely discussed. This is because every link in the supply chain is important, and warehouse costs are not a small figure. This applies to both suppliers and logistics companies. Achieving a reduction in warehouse costs is essential. The purpose of this study is to investigate the methods of optimizing logistics management through warehouse management and the impact on reducing the costs of operating activities of enterprises. The ABC model is useful in warehouse management, and there is a method similar to the ABC model that is also widely used. We can use the product churn data and then divide the goods according to the frequency of their arrival. This method will be discussed in detail in the essay. In addition to the above, there are many other affordable and easy ways. For example, changing the packaging and using recyclable packaging to save warehouse space, determining the utilization rate of warehouse equipment and checking frequently to make sure it has been fully utilized, developing a new intelligent information system to remind you to replenish goods, and so on. Warehouse management must meet the needs of the entire supply chain, which makes full use of modern technology to manage inventory, sorting, packaging, distribution, importation and exportation of goods in a particular tangible or intangible location. Of course, the ways to reduce warehouse costs are not limited to the above points. In general, if an enterprise is willing to pay attention to its warehouses, it can explore many cost-cutting opportunities. Thus, it can be concluded that an enterprise should not only focus on its internal warehouses, but also not ignore the external warehouse and the supplier's warehouse. If each warehouse can take the initiative to reduce costs, the enterprise can have great economic benefits. As warehouse costs are reduced, the supply chain can also be improved. A warehouse cannot live without information systems. Warehouse management systems often use automatic data capture (AIDC) technology, such as barcode scanners, mobile computers, wireless local area networks, and possibly radio frequency identification (RFID) to effectively monitor the flow of goods.
Logistics resource management: impact on cost reduction and productivity increase
Keywords: логістика; logistics; управління; management; витрати; costs; оптимізація; optimization; ресурси; resources; продуктивність; productivity